Memory Formation in Reversal Learning of the Honeybee - Hadar, Ravit; Menzel, Randolf (Frontiers in Behavioral Neuroscience, 2010)
In reversal learning animals are first trained with a differential learning protocol, where they learn to respond to a reinforced odor (CS+) and not to respond to a nonreinforced odor (CS-). Once they respond correctly to this rule, the contingencies of the conditioned stimuli are reversed, and animals learn to adjust their response to the new rule. This study investigated the effect of a protein synthesis inhibitor (emetine) on the memory formed after reversal learning in the honeybee Apis mellifera. Two groups of bees were studied: summer bees and winter bees, each yielded different results. Blocking protein synthesis in summer bees inhibits consolidation of the excitatory learning following reversal learning whereas it blocked the consolidation of the inhibitory learning in winter bees. These findings suggest that excitatory and inhibitory learning may involve different molecular processes in bees, which are seasonally dependent.